Molybdenum disulfide nanosheets embedded with nanodiamond particles: co-dispersion nanostructures as reinforcements for polymer scaffolds. (December 2019) - Feng, Pei; Kong, Ye; Yu, Li; Li, Yang; Gao, Chengde; Peng, Shuping; Pan, Hao; Zhao, Zhenyu; Shuai, Cijun
Highlights: Co-dispersion nanostructures were constructed by embedding nanodiamond particles into molybdenum disulfide nanosheets; ND particles were sandwiched between adjacent MoS2 nanosheets, which restrained the restacking of the MoS2 nanosheets; MoS2 nanosheets acted as steric hindrance layers, which prevented the aggregation of ND particles; The tensile and compressive strength of the scaffold were 94% and 52% higher than those of PHBV scaffold, respectively; The main strengthening mechanisms were crack deflection, crack bridging, crack pinning, and pulling out. Abstract: The aggregation of low-dimensional nanomaterials restricts their use as reinforcements in polymers. In this study, co-dispersion nanostructures were constructed by embedding nanodiamond (ND) particles into molybdenum disulfide (MoS2 ) nanosheets, and then were incorporated into poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) bone scaffolds that were fabricated via selective laser sintering. In the nanostructures, octahedral ND particles were sandwiched between adjacent MoS2 nanosheets, which restrained the restacking of the MoS2 nanosheets. Additionally, the MoS2 nanosheets acted as steric hindrance layers, which prevented the aggregation of octahedral ND particles. Experimental results demonstrated that the MoS2 nanosheets and ND particles were evenly dispersed in the PHBV matrix when 1 wt% of MoS2 and 2 wt% of ND were loaded at the same time, while the aggregation occurred when they were loaded individually. As a result, the scaffold with MoS2 and ND loading exhibited a 94% increase in tensile strength and 52% increase in compressive strength compared to a pure PHBV scaffold. The main strengthening mechanisms were crack deflection, crack bridging, crack pinning, and pulling out of MoS2 nanosheets and ND particles. In addition, the scaffold exhibited good cytocompatibility for cell adhesion, growth and spreading, as well as positive viability for cell proliferation.